EVALUATION AS A MEANS OF PERSUASION IN ENGLISH POLITICAL DISCOURSE - Abrahamyan, Samvel (Foreign Languages for Special Purposes, 2024)
The main goal of political discourse is to influence people and its main communicative strategy can be defined as the strategy of persuasion which involves such substrategies as manipulation, argumentation and evaluation. Evaluation / appraisal is an important part of the strategy of persuasion and is mainly connected with the affective domain. It includes such categories as attitude consisting of feelings, judgements and appreciations, as well as engagement and graduation. The research has shown that in English political discourse emotional evaluations and appraisals, both positive and negative, explicit and implicit, prevail over logical ones. Influenced by the basic semantic opposition of political discourse “we – they” and reflecting the relevant stance of the speaker, different types of evaluative statements tend to provoke in the audience feelings similar to those of the speaker, shape listeners’ perception, reinforce or change their cognition and opinion, predetermine their emotional reactions and actions.
Keywords: Evaluation; persuasion; manipulation; argumentation; political discourse